Respuesta :

Firstly, we can distribute both sides, this gives us 5x + 2x - 6 = -2x + 2. Next, we can combine our like terms. 7x - 6 = -2x + 2. The second option, B, is our answer.
sgo

Answer:

7x - 6 = -2x + 2

Step-by-step explanation:

Hi! First we are going to distribute our "2" and "-2" values to the values in parenthesis.

5x + 2x - 6 = -2x + 2

Now, we can combine our like terms, "5x" and "2x".

7x - 6 = -2x + 2

Since our problem's answers are left in this form, not completely combined our answer is 7x - 6 = -2x + 2.

Hope this Helps! :)

Have any questions? Ask below in the comments and I will try my best to answer.

-SGO